2021
DOI: 10.25105/jat.v8i1.7631
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Intellectual Capital Disclosure Dan Profitabilitas Terhadap Nilai Perusahaan

Abstract: <p>The Companys value reflects the assets owned by the company. This study aims to examine the effect of intellectual capital disclosure and profitability on firm value. The Population are manufacturing companies listed on the Indonesia Stock Exchange in 2014 2018. The samples of this study are forty-four companies listed in Indonesia Stock Exchange (IDX) selected by using purposive sampling method. Data analysis method used is multiple regression model. Based on the hypothesis tasted proves that the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
23

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 6 publications
1
4
0
23
Order By: Relevance
“…The effect of profitability on tax aggressiveness with intellectual capital as a moderator, as examined by Wibowo & Yuliana (2020) and Rivandi & Septiano (2021), showed that intellectual capital has a significant positive effect on and can moderate the relationship between profitability and company value. Intellectual capital has the potential to provide company value, increase profitability and assist companies in fulfilling their tax obligations.…”
Section: Profitability Intellectual Capital Tax Aggressivenessmentioning
confidence: 99%
“…The effect of profitability on tax aggressiveness with intellectual capital as a moderator, as examined by Wibowo & Yuliana (2020) and Rivandi & Septiano (2021), showed that intellectual capital has a significant positive effect on and can moderate the relationship between profitability and company value. Intellectual capital has the potential to provide company value, increase profitability and assist companies in fulfilling their tax obligations.…”
Section: Profitability Intellectual Capital Tax Aggressivenessmentioning
confidence: 99%
“…Masa-masa sulit yang dihadapi oleh perusahaan membuat internal perusahaan harus berupaya untuk mempertahankan kinerjanya sehingga kesejahteraan karyawan tetap terjaga. Kesejahteraan karyawan ini dapat ditingkatkan melalui kinerja perusahaan yang baik (Rivandi & Septiano, 2021).…”
Section: Pendahuluanunclassified
“…Profitabilitas yang terus meningkat tercatat dalam laporan keuangan menandakan kemampuan perusahaan semakin baik, hal itu dapat menggambarkan kekayaan perusahaan (Rivandi & Septiano, 2021). Profitabilitas perusahaan juga dianggap sebagai gambaran dari kinerja manajemen dalam mengelola perusahaan.…”
Section: Pendahuluanunclassified